Cytoreductive interventions in combination with hyperthermic intraperitoneal chemoperfusion in pseudomyxoma - A. G. Abdullayev; V. A. Gorbunova; M. D. Ter-Ovanesov; B. E. Polotsky; Yu. V. Buidenok; M. I. Davydov (Опухоли женской репродуктивной системы, 2014)
The tolerability and efficiency of peritonectomy in combination with hyperthermic intraperitoneal chemoperfusion were studied in patients with pseudomyxoma peritonei. Data from 10 patients were analyzed. The pattern of complications classified as surgical and chemotherapy- associated ones is presented. The long-term results of treatment are demonstrated.